The Effect of Agnihotra Ash In Commercial Diet on Weight External Offalof Broiler Chickens On The Age Of 5 Weeks - I M. O., Priana; Siti, N W.; Sukmawati, N. M.S. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study aims to determine the effect of Agnihotra ash in commercial diet on the weight external offal of broiler chickens on the age of 5 weeks.It was conducted in the cage owned by Mr. I Ketut Sunatra located at Br. Anyar, Kediri, Tabanan,Bali. There were 80 day old chicks CP 707 (unsexed) used in the study.The animal were bought at PT. Tohpati Poultry Shop, Denpasar – Bali. The experimental design used was Completely Randomized Design (CRD) consisted of 4 treatments and 4 replicates. So, there were 16 of experimental units. The treatments were: A = commercial diet without Agnihotra ash (control), B = Commercial diet + 0.1% Agnihotra ash, C = Commercial diet + 0.2% Agnihotra ash and D = Commercial diet + 0.3% Agnihotra ash. The variables observed were weight of head, neck, foot, blood and feather. The results showed that Agnihotra ash on the level of 0.1%-0.3% in commercial diet not significanly increase (P>0,05) the weight of external offal broiler aged 5 weeks. Based on the results of this study it can be concluded that Agnihotra ash at the level of 0.1%-0.3% in diet did not affect on external offal (the weight of head, neck, leg, blood and feather) broiler on the age of 5 weeks.   Keywords: Broiler, external offal, Agnihotra ash